Dc/Dc Converter For One Photovoltaic Panel With Fully Digital Control - Benda, Dušan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
The paper deals with the topic of design and realization of full digital control DC/DC converter for one photovoltaic panel with a 250 W peak power. A flyback topology with a non traditional snubber circuit was selected for the DC/DC converter.
Keywords: Switching mode power supply; flyback; passive snubber; digital control; MPPT